Pengaruh Green Accounting , Enviromental Performance, dan Corporate Governance Terhadap Kualitas Laporan Keberlanjutan pada Perusahaan Manufaktur di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the influence of Green Accounting, Environmental Performance, and Corporate Governance on the Quality of Sustainability Reports in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Report quality is measured by the completeness and transparency of disclosures based on GRI Standards. A quantitative method is employed, using a purposive sample of manufacturing firms from the 2020- 2023 period. Data is analyzed using multiple regression analysis. Green Accounting is proxied by environmental costs, Environmental Performance by PROPER ratings, Corporate Governance by the proportion of independent commissioners and institutional ownership, while report quality is measured through content analysis. The hypothesized results indicate that all three independent variables are expected to have a significant positive effect on Sustainability Report Quality. The implementation of green accounting, good environmental performance, and strong governance are predicted to enhance the quality of sustainability disclosures. This research contributes to environmental accounting literature and offers practical implications for regulators, investors, and corporate management in the context of ESG (Environmental, Social, and Governance) reporting.